Leptin interferes with 3',5'-Cyclic Adenosine Monophosphate (cAMP) signaling to inhibit steroidogenesis in human granulosa cells - HoYuen Basil; Cheng Linan; Chen Junling; Poon Song; Lin Qing; Leung Peter CK (BMC, 2009)
Abstract Background Obesity has been linked to an increased risk of female infertility. Leptin, an adipocytokine which is elevated during obesity, may influence gonadal function through modulating steroidogenesis in granulosa cells. Methods The effect of leptin on progesterone production in simian virus 40 immortalized granulosa (SVOG) cells was examined by Enzyme linked immunosorbent assay (ELISA). The effect of leptin on the expression of the steroidogenic enzymes (StAR, P450scc, 3betaHSD) in SVOG cells was examined by real-time PCR and Western blotting. The mRNA expression of leptin receptor isoforms in SVOG cells were examined by using PCR. SVOG cells were co-treated with leptin and specific pharmacological inhibitors to identify the signaling pathways involved in leptin-reduced progesterone production. Silencing RNA against leptin receptor was used to determine that the inhibition of leptin on cAMP-induced steroidogenesis acts in a leptin receptor-dependent manner. Results and Conclusion In the present study, we investigated the cellular mechanisms underlying leptin-regulated steroidogenesis in human granulosa cells. We show that leptin inhibits 8-bromo cAMP-stimulated progesterone production in a concentration-dependent manner. Furthermore, we show that leptin inhibits expression of the cAMP-stimulated steroidogenic acute regulatory (StAR) protein, the rate limiting de novo protein in progesterone synthesis. Leptin induces the activation of ERK1/2, p38 and JNK but only the ERK1/2 (PD98059) and p38 (SB203580) inhibitors attenuate the leptin-induced inhibition of cAMP-stimulated StAR protein expression and progesterone production. These data suggest that the leptin-induced MAPK signal transduction pathway interferes with cAMP/PKA-stimulated steroidogenesis in human granulosa cells. Moreover, siRNA mediated knock-down of the endogenous leptin receptor attenuates the effect of leptin on cAMP-induced StAR protein expression and progesterone production, suggesting that the effect of leptin on steroidogenesis in granulosa cells is receptor dependent. In summary, leptin acts through the MAPK pathway to downregulate cAMP-induced StAR protein expression and progesterone production in immortalized human granulosa cells. These results suggest a possible mechanism by which gonadal steroidogenesis could be suppressed in obese women.